The outcome and cost-effectiveness of nurse-led care in the community for people with rheumatoid arthritis: a non-randomised pragmatic study. Issue 8 (25th August 2015) - Watts, Richard A; Mooney, Janice; Barton, Garry; MacGregor, Alex J; Shepstone, Lee; Irvine, Lisa; Scott, David G I
Abstract : Objective: To determine the outcome and cost-effectiveness of nurse-led care in the community for people with rheumatoid arthritis (RA). Design: Non-randomised pragmatic study. Setting: Primary (7 primary care practices) and secondary care (single centre) in the UK. Methods: In a single area, pragmatic non-randomised study, we assessed the outcome, cost-effectiveness of community-based nurse-led care (NLC) compared with rheumatologist-led outpatient care (RLC). Participants were 349 adults (70% female) with stable RA assessed at baseline, 6 and 12 months. In the community NLC arm there were 192 participants. Outcome was assessed using Stanford Health Assessment Questionnaire (HAQ). The economic evaluation (healthcare perspective) estimated cost relative to change in HAQ and quality-adjusted life years (QALY) derived from EQ-5D-3L. We report complete case and multiple imputation results from regression analyses. Results: The demographics and baseline characteristics of patients in the community group were comparable to those under hospital care apart from use of biological disease-modifying antirheumatic drugs (DMARDS), which were adjusted for in the analysis. The mean incremental cost was estimated to be £224 less for RLC compared to the community NLC, with wide CIs (CI –£213 to £701, p=0.296). Levels of functional disability were not clinically significantly higher in the community NLC group: HAQ 0.096 (95% CI −0.026 to 0.206; p=0.169) and QALY 0.023 (95% CI −0.059 to 0.012; p=0.194). Conclusions: The results suggest that community care may be associated with non-significant higher costs with no significant differences in clinical outcomes, and this suggests a low probability that it is cost-effective.